Corporate Governance Compliance Model: The Extent to Which Financial Institutions have Complied with the Reserve Bank of Zimbabwe (RBZ) Corporate Governance Guideline No. 01-2004/BSD of 2004 - Mawanza, Wilford; Santu, Tinevimbo Chokuda; Mdlongwa, Sibonile (International Review of Management and Marketing, 2018)
The study sought to evaluate the extent of compliance by listed banking institutions to the Reserve Bank of Zimbabwe corporate governance guidelines of 2004. The research sample comprised of five listed banks. Secondary data was collected through content analysis technique, thus use of financial institution's annual report was made for period covering 2013-2015.The model developed in this research was applied to each of these banks and a compliance classification score was awarded. Results indicated that 20% of financial institutions did not comply with the RBZ corporate governance guidelines in relation to board meetings. Findings also revealed that the board composition of banks on the ZSE was in compliance with the RBZ guideline which stipulates that each banking institution shall have a minimum of five directors and the maximum of the study was five. It was concluded that there was high compliance rate in Zimbabwean banks to corporate governance principles on board composition, risk management, remuneration, audit committee and code of ethics. It was recommended that the Reserve Bank of Zimbabwe should continuously supervise banks on corporate governance guidelines requirements and best practices so as to avoid bank closure and also to stabilize the financial sector. Keywords: Corporate Governance, model, Compliance, Zimbabwe, Reserve Bank, Financial sector. JEL Classifications: G30, G33